Investigating the Difference in Demotivation Factors: A Case Study of Two Groups of Indonesian EFL Learners. - Reza Anggriyashati Adara; Nuryadi Nuryadi; Rahmat Ade Nasution (English Department - University of Sultan Ageng Tirtayasa, 2019)
Investigating demotivation factors of two different groups of EFL learners might provide more insights to reduce demotivation among students. Nevertheless, there is lack of studies toward demotivation, especially ones that analyze demotivation of Indonesian’s EFL students. Adara (2018) analyzed demotivation factors of a group of EFL students in Bekasi. However, her study only focused on one group of learners and did not compare demotivation factors which may affect different group of learners. Therefore, the present study aims to investigate the differences in demotivation factors of two groups of Indonesian EFL learners. Whereas one group consists of 44 English literature college students, another group is 41 students major in communication study. Applying a mixed-method approach to obtain the results, the present study distributed a set of questionnaires adapted from Sakai and Kikuchi (2009) to two groups of college students whereas the interviews were administered to six of them. The results indicate that both groups of learners were mostly demotivated by teachers’ incompetence and teaching styles, lack of intrinsic motivation, and inadequate school facilities. The results of present study suggest the importance of teachers’ roles in providing appropriate teaching approach for learners as well as learning content and materials to avoid students’ demotivation.